Compliant, Heterogeneously Integrated GaAs Micro‐VCSELs towards Wearable and Implantable Integrated Optoelectronics Platforms. Issue 4 (8th February 2014) - Kang, Dongseok; Lee, Sung‐Min; Li, Zhengwei; Seyedi, Ashkan; O'Brien, John; Xiao, Jianliang; Yoon, Jongseung
<x xml:space="preserve">Abstract</x> Vertical cavity surface emitting lasers (VCSELs) represent a ubiquitous light source with unique performance characteristics that excel for edge‐emitting lasers or light‐emitting diodes. VCSELs are available, however, mostly on growth wafers in rigid, planar formats over restricted areas, thereby frustrating their use for applications that benefit greatly from unconventional design options including large‐scale, programmable assemblies on unusual substrates, hybrid integration with dissimilar materials and devices, or mechanically compliant constructions. Here, materials design and fabrication strategies are presented to overcome these limitations of conventional VCSELs and create new application opportunities that are unavailable with existing technologies. Specialized epitaxial design and fabrication processes, together with printing‐based integration methods, enable defect‐free release of ultrathin, microscale VCSELs and their device‐level implementation on non‐native substrates in a scalable, cost‐effective fashion. Demonstrations of large‐scale, addressable arrays of VCSELs on plastics for flexible near‐infrared laser displays, and heterogeneous assemblies with silicon‐based electronics to form integrated optoelectronic sensors, illustrate unique capabilities.